2021
DOI: 10.3390/jcm10214878
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Uterine Adenomyosis: Medical vs. Surgical Approach

Abstract: Uterine adenomyosis is a commonly encountered estrogen-dependent disease in reproductive-age women, causing heavy menstrual bleeding, intense pelvic pain, and infertility. Although adenomyosis was previously considered a disease of multiparous women, it is becoming increasingly evident that it also affects younger nulliparous women and may compromise their fertility potential. It is clear that hysterectomy, the standard approach to definitively manage the disease, is not an option for patients wishing to prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 98 publications
0
19
0
2
Order By: Relevance
“…Due to the lack of knowledge pertaining to the molecular bases of the pathogenesis of adenomyosis currently available, diagnostic and treatment options are limited [ 16 , 17 , 18 ]. Recent studies have shown similarities with deep endometriosis at the histological level [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of knowledge pertaining to the molecular bases of the pathogenesis of adenomyosis currently available, diagnostic and treatment options are limited [ 16 , 17 , 18 ]. Recent studies have shown similarities with deep endometriosis at the histological level [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The success of conservative treatment requires a combination of long-term medical therapy or surgical therapy. In addition to the treatments used in this study, new GnRH antagonists are available [ 30 32 ], but as with GnRH agonists, the problem of side effects such as loss of bone density due to long-term administration remains. There are also some reports that uterine artery embolization and high-intensity focused ultrasound therapy are useful and safe as alternative therapies [ 33 ], but there is no randomized controlled trial, and the prognosis of pregnancy is unclear, so further verification is needed.…”
Section: Discussionmentioning
confidence: 99%
“…They have a favourable therapeutic profile because of their water-soluble properties, oral absorption and lower side effects if supplied in low doses [26 ▪ ]. Recent studies have demonstrated promising effectiveness in uterine volume reduction through lesion regression and associated adenomyosis symptoms decline [45 ▪▪ ,46 ▪ ].…”
Section: Management Optionsmentioning
confidence: 99%
“…European Society of Human Reproduction and Embryology (ESHRE) guidelines recommend concomitant use of aromatase inhibitors and oral contraceptives, progestogens or GnRH agonists in patients with pain associated with drug-resistant and surgery-resistant rectovaginal endometriosis [51]. However, there is neither current evidence nor an international consensus on the use of aromatase inhibitors for adenomyosis management [46 ▪ ]. Nevertheless, an older prospective study of 32 patients that compared effectiveness of letrozole to GnRH agonists for adenomyosis management has shown significant reduction in uterine volume posttreatment in both groups [52].…”
Section: Management Optionsmentioning
confidence: 99%